HUBUNGAN PERAN GANDA DAN STRES KERJA DENGAN KINERJA PERAWAT WANITA DI RSUD PADANG PARIAMAN - Esti, Amira; Ahmalia, Renty; Azkia, Annisa (Ensiklopedia of Journal, 2024)
The performance of female nurses can be affected by work stress. This is because it refers to two or more roles that are carried out simultaneously, in this case the role of women as wives for their husbands, mothers for their children, and roles as career women. This study aims to determine the relationship between multiple roles and work stress with the performance of female nurses in the Padang Pariaman Hospital Inpatient Room. This type of quantitative research with a Cross Sectional Study approach.  The research was conducted in July-August 2023 at the Padang Pariaman Hospital Inpatient Room. The research sample was 51 people. Sampling by means of Total Sampling. Statistical test using Chi Square degrees of significance (p value <α 0.05), with result 0,002.   The results showed that most of the respondents, namely 30 (56.1%), experienced high multiple roles. The majority of respondents, namely 36 (70.6%), experienced work stress in the light category. Most of the respondents, namely 32 (62.7%), had good performance.  Conclusion. There is a significant relationship between multiple roles and work stress with the performance of nurses at Padang Pariaman Hospital in 2023.Keywords : Double Role, Work Stress, Performance Of  Female Nurses